Criminal Justice Policy Strategies for Maine - McEwen, Craig; Hanneman, Evelyn (Maine Policy Review, 1996)
Is Maine controlling crime in ways that may lead to reductions in crime rates as well as a criminal justice system that is more cost-efficient to support? Craig McEwen and Evelyn Hanneman indicate we are not and ask the question: Can Maine take advantage of its relatively low crime rate to rethink and improve crime control strategies? In answering this question McEwen and Hanneman present a forceful argument for restorative justice, where repairing the harm to victims and communities becomes the forefront of our response to crime. They suggest six strategies to achieve this change, including the planned closing of the Maine State Prison.